THE EFFECTIVENESS OF BUSY TABLE TOWARDS CHILDREN’S LEARNING PERFORMANCE - Ahmad, Farah Najiha; Seman, Noor Ashikin; Othman, Zainudin; Ab Rahman, Siti Rokiah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study explores the effectiveness of busy tables as an interactive learning tool in enhancing children's learning performance in kindergarten settings. Busy tables, which incorporate a variety of hands-on activities designed to engage young learners, have gained popularity in early childhood education environments. The research investigates how busy tables influence cognitive, motor, and social skills development among preschool-aged children. By providing opportunities for sensory exploration, problem-solving, and collaborative play, busy tables are believed to support holistic development in ways that traditional learning tools may not. Data was collected through questionnaire, conducted in multiple kindergarten classrooms. The findings suggest to provide insights into how integrating busy tables into preschool classrooms can positively impact children's overall learning performance. Further research is recommended to explore how specific busy table designs and activity types may optimize learning outcomes in diverse educational settings.